Determination of pomological characteristics of some local and foreign almond cultivars in Yayladagy (Hatay) ecological conditions - Polat A.A.; Durgaç C.; Kamiloglu O. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
This study was carried out during the years between 1996 and 1998. The aim of this study was to determine the performance of three local types (48-1, 48-5 and 101-9) selected from different regions of Turkey and two foreign (Texas, Nonpareil) almond cultivars under Yayladag´y (in the Eastern Mediterranean Region of Turkey) ecological conditions. In the experiment, weight, width lengths and heights, as shelled nuts and kernel, width of shell and kernels ratio were measured and calculated. The in-shell almond and kernel weight and shelling percentage in the almond types and cultivars under study were 4.10-7.09 g, 1.41- 2.72 g and 27.95-47.16 per cent, respectively.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)